KENDALI PERALATAN LISTRIK DENGAN SMS MENGGUNAKAN ARDUINO DAN GPRS SHIELD - Andri Agus Agus S; Zulkifli Zulkifli; Rendra Gustriansyah (UNIVERSITAS INDO GLOBAL MANDIRI)
In the current era, the technology continues to evolve to facilitate human work, solve problems more quickly and accurately, the technology also can be used as the setting and control, whether using wired, wireless to the remote control. Setting or control would be better if done quickly, accurately and can be controlled remotely, especially the existing equipment at home when left by their owners. To simplify the control of the made design simulation controls that can control household electric appliances. In utilizing the communication medium is now able to reach almost all parts of Indonesia, by utilizing GPRS (General Packet Radio Service) provided by the mobile network operator, then made a design that can control the electrical equipment remotely using SMS (Short Message Service ) to facilitate the work, avoid direct contact dangerous if applied to equipment that is dangerous, saving human resources, time, cost and energy.